Consumer satisfaction towards housing by a property development and construction company in Sarawak - Heng, Christopher Yong Wei (Universiti Malaysia Sarawak (UNIMAS), 2013)
As one of the major property development and construction company in Sarawak, it is important for the company to be in touch with its buyers and it should also be very concerned and interested about the level of satisfaction among its buyers. Therefore in this study, the objectives are to determine the level of satisfaction in housing by the company among the house owners and to identify the attributes of housing that the owners consider as importan~Primary data was gathered from the Taman Riveria which is the case study and sampling reflects the composition of type of housing there. The main issues looked at are the characteristics of the ideal home, the house quality and the housing area. From the data analysis done, it was found that the vast majority of the respondents want to have a house which is safe in terms of security and free from natural disasters such as flooding and it must be located near school and places of worship. In terms of investment or capital appreciation, it is not a major concern. The one least important characteristic that the respondents look at is the public transportation serving the housing area. Generally, house buyers are satisfied with the house quality except for the kitchen size and the overall house design and colour scheme. Therefore, the company must take note and steps to improve upon those shortcomings.